Uji Daya Hambat Sari Bawang Putih (Allium Sativum) Terhadap Pertumbuhan Jamur Malassezia furfur Menggunakan Metode Difusi Kertas Cakram - chelyn mareli sarungu (Akademi Kesehatan John Paul II Pekanbaru, 2023)
Malassezia furfur is a dimorphic fungus that is lipophilic and causes pityriasis versicolor. People who experience pityriasis versicolor usually treat with oral treatments such as ketocenazole, itraconazole, fluconazole and tropical treatments such as 2.5% sulfide shampoo. Treatment like this is not free from side effects if there is repeated infection and long-term use of drugs without a doctor's prescription so that it can cause resistance. Therefore, other alternative treatments use natural medicines. One of them is garlic (Allium Sativum). Garlic has the main active compound content is Allicin, then other active compounds are essential oils, alkaloids, tannins, saponins, and flavonoids. The purpose of the study was to determine the ability of garlic (Allium Sativum) at various concentrations of 70%, 75%, 80%, 85%, 90% against the growth of Malassezia furfur fungus. The research design is true experiment post test only with control. This study uses the agar diffusion method with paper discs. The results of this study are garlic juice (Allium Sativum) concentration of 80% has the ability to inhibit the growth of Malassezia furfur with an inhibition zone of 46.23 mm which has effectiveness with imidazole ketocenazole group drugs.